Journal Review: A Review of Leadership in The Workplace Setting - Risiana; Mettalia Tania; Hanifah (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
Leadership is important in an organization, and the type of leadership used can also affect employee job satisfaction in an organization, which also affects employee performance. Therefore, applying the right leadership style according to organizational conditions is important to increase employee performance and job satisfaction. This paper aims to review leadership styles in different work settings. The method used in this study is Journal Review. This study found that in the first journal, the researcher found that Servant Leadership had a positive effect on job satisfaction among academic workers, and in the second journal it was found that there was a positive relationship for leaders who could control their emotions with the method of exchanging roles with employees to increase employee performance. In the first journal, 5 Dimensions of Servant Leadership has a positive relationship to job satisfaction in the academic workforce, and in the second journal, it was found that there is an influence on leaders who control their emotions with the performance of their employees.